RANCANGAN LEAN WAREHOUSING UNTUK ELIMINASI WASTE DAN MENINGKATKAN PRODUKTIVITAS KINERJA GUDANG PADA PT X SEBAGAI THIRD PARTY LOGISTICS (3PL) - Sari Rahayu, Gadis; Handayani, Melia; Ma'ruf, Ma'ruf (Penerbit Lafadz Jaya, 2026)
In the competitive supply chain era, PT X as a 3PL faces warehouse inefficiencies at WH-3, with fluctuating tyre inbound causing overcapacity, pallet pile-ups, and disrupted material flows. This study aims to classify dominant wastes using VSM and PAM, design a lean warehousing future state to eliminate wastes, and enhance warehouse productivity. It employs a quantitative descriptive method, with population as all WH-3 warehousing activities (inbound, inventory, outbound domestic/export) and purposive sampling of 32 work units from 50-100 observations (August-November 2025). Instruments include structured observation guidelines; analysis techniques encompass adequacy/uniformity tests, performance rating, standard time calculation, VSM, PAM, and fishbone diagrams. Results reveal dominant wastes: waiting (25%) and transportation (19%), mainly in export outbound, reducing lead time from 145 to 52 minutes and boosting PCE from 68% to 89% via future state design. In conclusion, lean warehousing integration effectively minimizes wastes and sustains 3PL competitiveness, recommending phased digitalization and layout zoning implementation.